(untitled) (De Legibus - Law Journal, 2025)
In this paper, we will briefly analyse the framework for the criminal liability of military superiors in order to critically assess the Bemba case, in particular the concept of ‘remote commander’. This concept was used as one of the grounds for the International Criminal Court’s decision to acquit Jean-Pierre Bemba Gombo of all the crimes of which he was accused. To this end, after a brief excerpt on the evolution of the institute of the criminal responsibility of hierarchical superiors and its legal nature, we will look at the various requirements enshrined in Article 28(a) of the Rome Statute of the International Criminal Court and the respective doubts that arise regarding their fulfilment. Finally, we will go through the Bemba case, summarising the context in which the facts occurred, the 2016 conviction decision and the 2018 acquittal decision. In the latter, we will focus on the problems surrounding the concept of ‘remote commander’.